Oncostatin-M inhibits luteinizing hormone stimulated Leydig cell progenitor formation in vitro - de Boer-Brouwer Mieke; De Miguel Maria P; van Dissel-Emiliani Federica MF; Teerds Katja J; Körting Lina M; Rijntjes Eddy (BMC, 2007)
Abstract Background The initial steps of stem Leydig cell differentiation into steroid producing progenitor cells are thought to take place independent of luteinizing hormone (LH), under the influence of locally produced factors such as leukaemia inhibitory factor (LIF), platelet derived growth factor A and stem cell factor. For the formation of a normal sized Leydig cell population in the adult testis, the presence of LH appears to be essential. Oncostatin M (OSM) is a multifunctional cytokine and member of the interleukin (IL)-6 family that also includes other cytokines such as LIF. In the rat OSM is highly expressed in the late fetal and neonatal testis, and may thus be a candidate factor involved in Leydig cell progenitor formation. Methods Interstitial cells were isolated from 13-day-old rat testes and cultured for 1, 3 or 8 days in the presence of different doses of OSM (range: 0.01 to 10 ng/ml) alone or in combination with LH (1 ng/ml). The effects of OSM and LH on cell proliferation were determined by incubating the cultures with [3H]thymidine or bromodeoxyuridine (BrdU). Developing progenitor cells were identified histochemically by the presence of the marker enzyme 3beta-hydroxysteroid dehydrogenase (3beta-HSD). Results OSM, when added at a dose of 10 ng/ml, caused a nearly 2-fold increase in the percentage of Leydig cell progenitors after 8 days of culture. Immunohistochemical double labelling experiments with 3beta-HSD and BrdU antibodies showed that this increase was the result of differentiation of stem Leydig cells/precursor cells and not caused by proliferation of progenitor cells themselves. The addition of LH to the cultures consistently resulted in an increase in progenitor formation throughout the culture period. Surprisingly, when OSM and LH were added together, the LH induced rise in progenitor cells was significantly inhibited after 3 and 8 days of culture. Conclusion Taken together, the results of the present study suggest that locally produced OSM may not only play a role in the regulation of Sertoli cell proliferation and the initiation of spermatogenesis but may also play a role in the regulation of Leydig cell progenitor formation by keeping the augmenting effects of LH on this process in abeyance.